ANTESEDEN PERILAKU BERBAGI PENGETAHUAN DAN PENGARUHNYA PADA KEMAMPUAN INOVASI PERUSAHAAN - KHOIRUR ROZAQ (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2014)
This research analyzes the influence of attitude toward knowledge sharing, subjective norms regarding knowledge sharing, perceived behavior control on the intention to share knowledge and influence the intention to share knowledge, individual factors (enjoyment in helping others and knowledge self-efficacy), organizational factors (top management support and organizational reward) and the use of information and communication technologies in the knowledge sharing behavior and whether more leads to the company's innovation capabilities. The object of this study is PT. Bank Rakyat Indonesi (Persero) Tbk. Kantor Branch Sragen dan Bank Jateng Cabang Sragen. Research problem refers to the phenomenon of data on the two banks, which demonstrated the difficulty of applying the knowledge sharing behavior among peers. The problems that arise are: how to improve knowledge sharing behavior and whether to allow companies to improve innovation ability. A modeling has been built and eight research hypotheses have been formulated.Sample using convenience sampling method. The study used 257 respondents and all respondents are employees of BRI Branch Sragen and Bank Jateng Sragen. Data analysis using Structural Equation Models with computer programs Amos 6. The results of this study indicate that such Attitude toward knowledge sharing subjective norms regarding knowledge sharing, perceived behavior control positive influence on intention to share knowledge. intention to share knowledge, individual factors (enjoyment in helping others), and organizational factors (top management support and organizational reward) the behavior of knowledge sharing (Knowledge Donating and Knowledge Collecting). Knowledge Donating and Knowledge Collecting positive effect on the firms innovation capabilities.